Answer:
Shifts 4 units down --->
![g(x)=2x-10](https://img.qammunity.org/2021/formulas/mathematics/college/mvogyfi6bhyvyev56yzu2cmt7n7bpc3a1q.png)
Stretches f(x) by a factor of 4 away from x-axis--->
![g(x)=8x-6](https://img.qammunity.org/2021/formulas/mathematics/college/3jttc86ql5sj5h7tqukavr9u17ufspdg6y.png)
Shifts f(x) 4 units right--->
![g(x)=2x-14](https://img.qammunity.org/2021/formulas/mathematics/college/76764nschtgxyea84jmn3zfpegh9xaf96u.png)
Compress f(x) by a factor of 1/4 toward the y-axis --->
![g(x)=1/2x-3/2](https://img.qammunity.org/2021/formulas/mathematics/college/993ltp7ws2uli4pkdrhtseay48r9lmdus9.png)
Explanation:
We are given
![f(x)=2x-6](https://img.qammunity.org/2021/formulas/mathematics/middle-school/3ggd5nia1hknosrf7isgx6k8rxg8qopgi0.png)
We need to match the transformations.
1) shifts f(x) 4 units down.
When function f(x) shifts k units down the new function becomes f(x)-k
In our case
![g(x)=2x-6-4\\g(x)=2x-10](https://img.qammunity.org/2021/formulas/mathematics/college/yr9zlbkkd2jp17j7w79gtjqwg1owrtkeq4.png)
So, Shifts 4 units down --->
![g(x)=2x-10](https://img.qammunity.org/2021/formulas/mathematics/college/mvogyfi6bhyvyev56yzu2cmt7n7bpc3a1q.png)
2) Stretches f(x) by a factor of 4 away from x-axis
When function f(x) is stretched by a factor of b away from x-axis the new function becomes f(bx)
![g(x)=2(4x)-6\\g(x)=8x-6](https://img.qammunity.org/2021/formulas/mathematics/college/mtbid3drb10cdmg9k23uiluktwgkrwhbth.png)
So, Stretches f(x) by a factor of 4 away from x-axis--->
![g(x)=8x-6](https://img.qammunity.org/2021/formulas/mathematics/college/3jttc86ql5sj5h7tqukavr9u17ufspdg6y.png)
3) Shifts f(x) 4 units right
When function f(x) shifts h units right the new function becomes f(x-h)
![g(x)=2(x-4)-6\\g(x)=2x-8-6\\g(x)=2x-14](https://img.qammunity.org/2021/formulas/mathematics/college/w03u1h730s5b4cc0nvep5d2gwst2yrx0ky.png)
So, Shifts f(x) 4 units right--->
![g(x)=2x-14](https://img.qammunity.org/2021/formulas/mathematics/college/76764nschtgxyea84jmn3zfpegh9xaf96u.png)
4) Compress f(x) by a factor of 1/4 toward the y-axis
When function f(x) is compressed by h factor of a toward the y-axis the new function becomes h.f(x)
![g(x)=1/4(2x-6)\\g(x)=1/2x-3/2](https://img.qammunity.org/2021/formulas/mathematics/college/afg7wigzp5lly2yj4oa1u79ctik0ooy68f.png)
Compress f(x) by a factor of 1/4 toward the y-axis --->
![g(x)=1/2x-3/2](https://img.qammunity.org/2021/formulas/mathematics/college/993ltp7ws2uli4pkdrhtseay48r9lmdus9.png)
(Option Not given)
(If we compress f(x) by a factor of 4 towards y-axis we get g(x)=8x-24)